The Concept of "Love" in the Selected Romantic Poems:A Literary and Psychoanalytic Reading (Journal of Imam Al-Kadhim College, 2025)
This research paper examines several selected poems from the two Romantic eras to be literarily investigated using Eric Fromm's Theory. The purpose of this study is to demonstrate how literary analysis describes the poet's language. This research is based on five love poems written by eighteenth-century poets. This study also examines the progression of word formation during the Romance era, whether through losses, surviving characteristics, reorganisation processes, or the development of new structures. Psychological examination of the concepts of love include brotherly love, motherly and fatherly love, sensual love, self-love, and God's love, as well as an assessment of the breakdown of love in contemporary Romantic poetry. The goal is to identify the defining features that characterise the style of love poetry. During the literary analysis of each poem, a connection is made between the message delivered, and the tools and devices used to convey it.
Keywords: Eric Fromm, Literary Analysis, Love poems, Romanticism, Psychoanalysis